Clinical and histological study of permanent alopecia after bone marrow transplantation - Flávia Machado Alves Basilio; Fabiane Mulinari Brenner; Betina Werner; Graziela Junges Crescente Rastelli (Sociedade Brasileira de Dermatologia, 2015)
Abstract: BACKGROUND: Permanent alopecia after bone marrow transplantation is rare, but more and more cases have been described, typically involving high doses of chemotherapeutic agents used in the conditioning regimen for the transplant. Busulfan, classically described in cases of irreversible alopecia, remains associated in recent cases. The pathogenesis involved in hair loss is not clear and there are few studies available. In addition to chemotherapeutic agents, another factor that has been implicated as a cause is chronic graft-versus-host disease. However, there are no histopathological criteria for defining this diagnosis yet. OBJECTIVE: the study aims to evaluate clinical and histological aspects in cases of permanent alopecia after bone marrow transplantation, identifying features of permanent alopecia induced by myeloablative chemotherapy and alopecia as a manifestation of chronic graft-versus-host disease. METHODS: data were collected from medical records of 7 patients, with description of the clinical features and review of slides and paraffin blocks of biopsies. RESULTS: Two distinct histological patterns were found: one similar to androgenetic alopecia, non-scarring pattern, and other similar to lichen planopilaris, scarring alopecia. CONCLUSION: The first pattern corroborates the literature cases of permanent alopecia induced by chemotherapeutic agents, and the second is compatible with manifestation of chronic graft-versus-host disease on scalp, that has never been described yet. The results contribute to the elucidation of the factors involved in these cases, including the development of therapeutic methods